Pengaruh Perputaran Kas, Perputaran Piutang, dan Perputaran Persediaan Terhadap Profitabilitas pada Perusahaan Sub Sektor Makanan dan Minuman yang Terdaftar di Bursa Efek Indonesia Tahun 2020 – 2023 - Shella Fricilia Saragih; Retno Suliati Suleiman (IAI Nasional Laa Roiba Bogor, 2025)
This thesis aims to determine the effect of cash turnover, receivables turnover and inventory turnover on profitability in manufacturing companies listed on the Indonesia Stock Exchange in 2020 - 2023. This research uses independent variables, namely cash turnover, receivables turnover and inventory turnover. The dependent variable is profitability. The research period was taken for 4 years from 2020 to 2023. The research method uses methods with secondary data types. The results of the analysis in this research were that the descriptive statistical test was declared valid, in the normality test, there was no multicollinearity, no heteroscedasticity, the variables cash turnover, accounts receivable turnover and inventory turnover had an effect on ROA. Data was obtained from the annual financial reports of food and beverage sub-sector companies downloaded on the website www.idx.co.id.